2018
DOI: 10.1038/s41467-018-03698-8
|View full text |Cite
|
Sign up to set email alerts
|

Water-promoted C-S bond formation reactions

Abstract: Allylic sulfones, owning to their widespread distributions in biologically active molecules, received increasing attention in the past few years. However, the synthetic method under mild conditions is still a challenging task. In this paper, we report a sulfinic acids ligation with allylic alcohols via metal-free dehydrative cross-coupling. Both aliphatic and aromatic sulfinic acids react with various allylic alcohols to deliver the desired allylic sulfones in high yields with excellent selectivity. This carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
59
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(62 citation statements)
references
References 27 publications
1
59
0
Order By: Relevance
“…In the Raman spectra, the band at 1331 cm À 1 is assigned to the À NO 2 stretching vibration of pNTP, and the bands at 1571 cm À 1 and 1586 cm À 1 are CÀ C stretching vibration of the benzene ring of pNTP and pATP, respectively. [8,16] Such assignments are also confirmed by the Raman spectra of bulk pNTP and pATP ( Figure S2). From the result, we can see that as time goes on, the band at 1571 cm À 1 gradually decreases while the band at 1586 cm À 1 increases for all the catalysts (as shown in Figure S3a, such a trend can also be observed for 3.7 nm Pt when the reaction time is prolonged to 1400 s).…”
supporting
confidence: 65%
See 1 more Smart Citation
“…In the Raman spectra, the band at 1331 cm À 1 is assigned to the À NO 2 stretching vibration of pNTP, and the bands at 1571 cm À 1 and 1586 cm À 1 are CÀ C stretching vibration of the benzene ring of pNTP and pATP, respectively. [8,16] Such assignments are also confirmed by the Raman spectra of bulk pNTP and pATP ( Figure S2). From the result, we can see that as time goes on, the band at 1571 cm À 1 gradually decreases while the band at 1586 cm À 1 increases for all the catalysts (as shown in Figure S3a, such a trend can also be observed for 3.7 nm Pt when the reaction time is prolonged to 1400 s).…”
supporting
confidence: 65%
“…[7] Recently, surface-enhanced Raman spectroscopy (SERS) has been employed to in-situ monitor the catalytic reactions. [8] SERS has ultrahigh surface sensitivity due to the electromagnetic and chemical enhancement generated by the Au or Ag nanostructures, [9] allowing in situ study the catalytic reactions carried out on their surfaces. [10] The intermediate species and kinetics of the reaction, as well as the effect of the morphology and composition of the catalysts on them, can be studied in depth using in-situ SERS.…”
mentioning
confidence: 99%
“…Xie and Schlucker also demonstrated that hot electrons, generated by the non-radiative decay of LSPs, can be transferred to reactants. 46 Christopher et al 47,48 showed that hot electrons are involved in a number of oxidation reactions on plasmonic clusters of Ag nanocubes under low-intensity visible light illumination. Many studies devoted to water splitting, hydrogen evolution and oxygen evolution were recently reported [49][50][51][52] and reviewed.…”
Section: Plasmonic Electrochemistrymentioning
confidence: 99%
“…[13][14][15] For example, the dissociation of H 2 , water splitting, reduction of CO 2 , conversion of CO to CO 2 , degradation of pesticides, and so on. [16][17][18][19][20][21][22] Therefore, the surface plasmon played the dual roles in enhancing surface Raman signal and inducing the surface chemical reaction. By the integration of the giant enhancement and catalytic activities of plasmon, SERS has been developed as a promising technique to in situ monitor the plasmoninduced chemical reaction at molecular level.…”
Section: Introductionmentioning
confidence: 99%